2022
DOI: 10.3390/ijms23147688
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Aminothiazole Derivatives as Promising Antiviral, Antioxidant and Antibacterial Candidates

Abstract: It is well-known that thiazole derivatives are usually found in lead structures, which demonstrate a wide range of pharmacological effects. The aim of this research was to explore the antiviral, antioxidant, and antibacterial activities of novel, substituted thiazole compounds and to find potential agents that could have biological activities in one single biomolecule. A series of novel aminothiazoles were synthesized, and their biological activity was characterized. The obtained results were compared with tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…[43] Previously, we have synthesized a library of N,N-disubstituted β-aminoacids derivatives containing hydrazone and azole fragments and have evaluated their biological properties, which appeared to possess the convincing anticancer effect against triple-negative breast cancer and glioblastoma cells in vitro. [44] They demonstrated promising antimicrobial, [45][46][47][48] significant antibacterial, [49][50][51][52] and in addition, antiviral and antioxidant [51,52] activities.…”
Section: Introductionmentioning
confidence: 99%
“…[43] Previously, we have synthesized a library of N,N-disubstituted β-aminoacids derivatives containing hydrazone and azole fragments and have evaluated their biological properties, which appeared to possess the convincing anticancer effect against triple-negative breast cancer and glioblastoma cells in vitro. [44] They demonstrated promising antimicrobial, [45][46][47][48] significant antibacterial, [49][50][51][52] and in addition, antiviral and antioxidant [51,52] activities.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have synthesized a library of N,N-disubstituted β-aminoacids derivatives containing hydrazone and azole fragments and have evaluated their biological properties, which appeared to possess the convincing anticancer effect against triple-negative breast cancer and glioblastoma cells in vitro [35], demonstrated promising antimicrobial effect [36−39], as well as signi cant antibacterial [40−43], and in addition, antiviral and antioxidant [42,43] activities.…”
Section: Introductionmentioning
confidence: 99%
“…18 Thiazole is a five-membered heterocycle containing nitrogen and sulfur atoms, which is a widely prevalent component in natural products and anti-infective drugs. 19 Thiazole has attracted significant attention due to its remarkable properties. There have been many drugs containing thiazole successfully used in clinical applications, such as sulfathiazole and various cephalosporins.…”
mentioning
confidence: 99%
“…The findings demonstrated that the antibacterial activity of pleuromutilin could be improved by introducing a five-membered heterocyclic at the C14 side chain . Thiazole is a five-membered heterocycle containing nitrogen and sulfur atoms, which is a widely prevalent component in natural products and anti-infective drugs . Thiazole has attracted significant attention due to its remarkable properties.…”
mentioning
confidence: 99%